Sosialisasi KB Metode Kontrasepsi Jangka Panjang (MKJP) Implant Di Dusun 2 Desa wonokerto Kecamatan Tugumulyo Kabupaten Musi Rawas - Esa Nurmasari; Ekawati , Yuli; Sari, Lia Puspita; Sari, Fikitri Marya; Yulianti, Syami (Utami Publisher, 2025)
Family Planning (KB) is a strategic program in an effort to reduce birth rates and improve the quality of family life. One effective method is the Long-Term Contraceptive Method (MKJP) Implant. In Musi Rawas Regency, South Sumatra Province, the Percentage of Use of MKJP Implant KB is only 18%, especially in the Wonokerto Village area, Tugumulyo District, only 11 people use MKJP Implant KB out of 117 PUS. The Thematic Real Work Lecture Program (KKN-T) of Dehasen University Bengkulu in 2025 focuses on promotive efforts through an educational approach, namely with the Counseling method on MKJP Implant KB, distribution of leaflets and Digital education. This activity is carried out in coordination with village officials, KB counselors and the local community. This study aims to evaluate the impact of socialization on increasing PUS knowledge about the Long-Term Contraceptive Method (MKJP) Implant KB. Activities are carried out through an educational approach and direct counseling. The results show an increase in public knowledge and interest in MKJP implants. Socialization has proven to be effective as a promotive strategy in forming positive attitudes and increasing acceptor participation. Cross-sector collaboration and ongoing education are essential to support efforts to increase public knowledge and participation in the use of MKJP KB.